Intravenous Iron Sucrose Therapy for Iron Deficiency Anaemia in Pregnancy: Efficacy and Safety in Bangladeshi Women (Bangladesh Medical Journal, 2025)
Iron deficiency anaemia (IDA) remains a major public health concern among pregnant women in Bangladesh. Given the high prevalence of iron deficiency anaemia in pregnancy among Bangladeshi women injectable iron sucrose therapy during antenatal period may be effective in its treatment. The aim of this study was to evaluate the efficacy and safety of intravenous iron sucrose therapy in antenatal patients with IDA. A cross-sectional study was conducted among 150 pregnant women with mild to moderate IDA (Hb 7–9.9 g/dL, serum ferritin